Preadmission glucocorticoid use and anastomotic leakage after colon and rectal cancer resections: a Danish cohort study. Issue 9 (24th September 2015) - Ostenfeld, Eva Bjerre; Erichsen, Rune; Baron, John A; Thorlacius-Ussing, Ole; Iversen, Lene Hjerrild; Riis, Anders H; Sørensen, Henrik Toft
Abstract : Objective: To examine whether preadmission glucocorticoid use increases the risk of anastomotic leakage after colon and rectal cancer resections. Design: A population-based cohort study. Setting: Denmark (2001–2011). Participants: We identified patients who had undergone a primary anastomosis after a colorectal cancer resection by linking medical registries. Participants who filled their most recent glucocorticoid prescription ≤90, 91–365 and >365 days before their surgery date were categorised as current, recent and former users, respectively. Main outcome measures: We calculated 30-day absolute risk of anastomotic leakage and computed ORs using logistic regression models with adjustment for potential confounders. Results: Of the 18 190 patients with colon cancer, anastomotic leakage occurred in 1184 (6.5%). Glucocorticoid use overall was not associated with an increased risk of leakage (6.4% vs 6.9% among never-users; OR 1.05; 95% CI 0.89 to 1.23). Categories of oral, inhaled or intestinal-acting glucocorticoids did not greatly affect risk of leakage. Anastomotic leakage occurred in 695 (13.2%) of 5284 patients with rectal cancer. Glucocorticoid use overall slightly increased risk of leakage (14.6% vs 12.8% among never-users; OR 1.36, 95% CI 1.08 to 1.72). Results did not differ significantly within glucocorticoid categories. Conclusions: Preadmission glucocorticoids modestly increased the risk of anastomotic leakage mainly after rectal cancer resection. However, absolute risk differences were small and the clinical impact of glucocorticoid use may therefore be limited.